“Cybercrime”: Fenomena Kejahatan melalui Internet di Indonesia - Fuady, Muhammad (Mediator, 2005)
It had been long known that technology, as Janus, has two side of coins: the good side,and the bad side. Everybody knows the benefit of technology development. But there aren’t much who realize the negative potent of technology. Cybercrime discussed in this article is an example of how crime was developed sophisticatedly by using technological means. Cybercrime, simply defined as criminal acts using cyber and Internet, has faced a new challenge for lawmaker and law enforcement mission. In Indonesia, carding become serious issues to be combated. Another type of cybercrime frequently occur in Indonesia are hacking and deface. Although Internet user in Indonesia is estimated no more than 5% of total population (4.38 million persons), everybody must attended cybercrime issues seriously. The loss of cybercrime reached unspeakable heights and damaged public safety in communication and information flows.